PTU-100 The role of a multi-regional specialist multi-disciplinary meeting in diagnosis and management of igg4-related disease. (June 2019) - Goodchild, George; Peters, Rory; Cargill, Tamsin; Fadipe, Adetokunbo; Leando, Maria; Luqmani, Raashid; Sadler, Ross; Fryer, Eve; Firmin, Louisa; Rodriguez-Justo, Manuel; Bungay, Helen; Barnes, Eleanor; et al.
Abstract : Introduction: IgG4-related disease (IgG4-RD) is a complex multi-system fibroinflammatory disorder, often presenting to the gastroenterologist as autoimmune pancreatitis (AIP) and sclerosing cholangitis (IgG4-SC). It requires careful diagnostic differentiation from malignancy and other inflammatory disorders. The majority of patients have persistent inflammation despite best available treatments, and many who achieve clinical remission subsequently relapse, leading to organ dysfunction and failure. Diagnostic challenges arise from multi-organ cross-speciality presentation, absence of a single diagnostic test and a plethora of diagnostic guidelines, whilst management decisions are influenced by the older demographic and identification of subclinical disease. Methods: We established an inter-regional IgG4-RD specialist multi-disciplinary meeting (MDM) held six weekly via web-link between Oxford and UCLH, incorporating multiple specialists across medical, surgical, immunology, histopathology and radiology disciplines. We describe our first year experience (Nov 2016–Nov 2017). Results: Over one-year, 50 patients were referred to the IgG4-RD MDM. Of these 31/50 (62%) had multiple organ involvement and 32/50 (64%) had an elevated serum IgG4 (>1xULN). 36 (72%) were referred for diagnostic clarification, of whom 16 (44%) met diagnostic criteria for IgG4-RD (Boston and/or CDC) or AIP/IgG4-SC (HISORt), 9 (25%) did not meet diagnostic criteria but were considered to have 'possible' IgG4-RD and were managed as such, and 11 (31%) did not meet diagnostic criteria, and an alternative diagnosis was offered in 6/11. Of those diagnosed with IgG4-RD, 25 (64%) had management changes recormmended via the MDM, including treatment escalation (21; 3 of these had rituximab), de-escalation (4), conservative approach (14), further imaging and histology investigation (9), additional specialist opinion (3). Conclusions: We have demonstrated the value of a specialist IgG4-RD MDM incorporating a range of divesre specialists to aid diagnostic and management decsicions in a complex multi-system fibroinflammatory disease, providing a model for other centres across the UK.